2014
DOI: 10.1093/jjco/hyt235
|View full text |Cite
|
Sign up to set email alerts
|

Dose-volumetric Parameters for Predicting Hypothyroidism after Radiotherapy for Head and Neck Cancer

Abstract: The V45 may predict risk of developing hypothyroidism after radiotherapy for head and neck cancer, and a V45 of 50% can be a useful dose-volumetric threshold of radiation-induced hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
62
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 18 publications
8
62
0
3
Order By: Relevance
“…[3,5,6] In our study, The MRT independent of thyroid volume was 52.2 Gy. Differently, some studies reported that radiation dose-volumetric parameters could be a beneficial for post-RT HT.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…[3,5,6] In our study, The MRT independent of thyroid volume was 52.2 Gy. Differently, some studies reported that radiation dose-volumetric parameters could be a beneficial for post-RT HT.…”
Section: Discussionsupporting
confidence: 46%
“…Similarly, some studies reported that the median periods for development of HT were between eight and 16 (range, 1-96) months. [3,5,17] For this reason, these findings suggest that post-RT HT should be considered during the entire follow-up period, especially during the first 18 months.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations